Exercise Alleviates the Apolipoprotein A5-Toll-Like Receptor 4 Axis Impairment in Mice With High-Fat Diet-Induced Non-alcoholic Steatohepatitis - Yu, Yang; Yu, Lina; Cheng, Nuo; Liu, Xiaoguang; Fang, Chunlu; Liu, Shujing; Zhu, Lin (Frontiers in Physiology, 2021)
Background: Apolipoprotein A5 (ApoA5), an important modulator of plasma and hepatic triglyceride metabolism, has been found to be downregulated by metformin to improve nonalcoholic fatty liver disease. Meanwhile, exercise has been recommended as a therapeutic strategy for nonalcoholic steatohepatitis (NASH). However, no study has yet determined whether exercise affects hepatic ApoA5 expression or the inhibition of ApoA5 to toll-like receptor 4 (TLR4). We herein examined the effects of exercise on hepatic ApoA5 expression and the relevance of ApoA5 and TLR4-mediated pathway in mice with high-fat diet (HFD)-induced NASH. Methods: Male C57BL/6J mice were built NASH model with high-fat diet for 12 weeks, and following mice were subjected to exercise for 12 weeks on a treadmill. Microscopy and enzyme-linked immunosorbent assay were used to measure histological analysis of liver and hepatic lipids, respectively. Quantitative real-time PCR and western blot were used to determined mRNA and protein levels of ApoA5 and TLR4-mediated nuclear factor kappa B (NF-κB) pathway components, respectively. ApoA5 overexpression plasmids transfected into mice to investigate the relevance of ApoA5 and TLR4. Results: 12 weeks of exercise remarkably alleviated HFD-induced hepatic lipid accumulation, inflammation, and fibrosis, as well as reduced serum lipopolysaccharide (LPS), hepatic TLR4, myeloid differentiation factor 88 (MyD88), and NF-κBp65 expression. Importantly, exercise did not reduce ApoA5 expression but instead enhanced its ability to suppress TLR4-mediated NF-κB pathway components by decreasing circulating LPS in our experiments involving transfection of ApoA5 overexpression plasmids and LPS interventions. Conclusions: The results demonstrated that exercise improved HFD-induced NASH by triggering the inhibitory effects of ApoA5 on the TLR4-mediated NF-κB pathway.